Silicon nanowire with three-dimensional network structure as well as preparation method and application of silicon nanowire

By adding decentralizers and constructive agents to the silicon nano line and the solvent system, control the line length and surface activity performance of the silicon nan navile, realize the self -assembly of the three -dimensional mesh structure, and solve the problem of the clustering problem of the silicon nano wire in the lithium -ion battery , Improved electrochemical properties and suitable for large -scale production.

CN119361693APending Publication Date: 2025-01-24TOMI CHENGDU APPLIED TECH RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310855772.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the agglomeration problem of silicon nanowires in lithium-ion batteries, resulting in a decline in electrochemical performance and difficulty in achieving large-scale production.

Method used

By adding decentralizers and constructive agents to the silicon nano line and the solvent system, control the line length and surface activity performance of the silicon nan navile, prevent oxidation and structure reconstruction, realize the self -assembly of the three -dimensional mesh structure, prepare the dispersing uniform, stable structure, stable structure, and stable structure. Silicon nano -wire electrode material.

Benefits of technology

It improves the conductivity and cycle performance of silicon nanowires, reduces the volume expansion rate, is suitable for mass production, and provides a more stable electrode material for lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004337456940000131
    Figure BDA0004337456940000131
Patent Text Reader

Abstract

The invention provides a silicon nanowire with a three-dimensional network structure as well as a preparation method and application of the silicon nanowire. The preparation method comprises the following steps: (1) performing first mixing on a dispersing agent and a solvent, and then adding silicon nanowires for second mixing to obtain a mixed solution; (2) dispersing the mixed solution obtained in the step (1), and then separating to obtain an intermediate product; and (3) mixing the intermediate product obtained in the step (2) with a construction agent, carrying out hydrothermal reaction, and then grinding and crushing to obtain the silicon nanowire with the three-dimensional network structure. According to the preparation method of the silicon nanowire with the three-dimensional network structure, provided by the invention, the electron and ion transmission performance of the silicon nanowire is improved, the volume expansion rate of the silicon nanowire is reduced, and a basis is provided for subsequent processing treatment and application in a lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries and relates to a three-dimensional network structure silicon nanowire and a preparation method and application thereof. Background Art

[0002] Silicon nanowires (SiNWs) can exhibit excellent electrochemical performance as negative electrodes for lithium-ion batteries due to their unique one-dimensional structure. Compared with traditional silicon nanoparticles (SiNPs), they have lower volume expansion, better conductivity, less stress during lithium insertion and extraction, and less damage to the solid electrolyte interface (SEI) and material structure. Therefore, their electrochemical performance is better than that of SiNPs. In addition, the reversible capacity of SiNWs is 3000mAh g -1 As mentioned above, the first coulombic efficiency is usually greater than 87%, which greatly promotes the application of silicon-based materials.

[0003] The wire diameter of SiNWs prepared by gas-liquid-solid (VLS) can be controlled at 50-200nm and the length is 500-4000nm. However, its macroscopic state is a sponge with severe agglomeration and is difficult to disperse. In the process of preparing electrodes, SiNWs monomers cannot be evenly attached by adhesives, resulting in poor adhesion to the current collector and easy to fall off in subsequent electrochemical processes. SiNWs microscopic wires are too long and are easy to break during the process of lithium ion insertion and extraction, the ion and electron channels of the material are destroyed, and the balance of the electrode material is broken, resulting in a decrease in its electrochemical performance.

[0004] CN104003393A discloses a mechanical alloying assisted solid-liquid-solid method for preparing self-dispersed silicon nanowire powder, using Si powder and Ni powder as raw materials, adopting mechanical alloying to obtain a mixed powder of Ni-encapsulated Si structure, and then placing the mixed powder in a vacuum tube furnace to undergo a solid-liquid-solid insulation process to obtain a silicon nanowire powder with Ni core as the center and growing radially. The prepared silicon nanowires are characterized by self-dispersion, which solves the problems of easy entanglement, agglomeration and difficulty in dispersion of nanowires in traditional processes. However, the preparation of the mixed powder of Ni-encapsulated Si structure has relatively high technical requirements, and is currently only applicable to laboratory research and cannot be achieved in large-scale production.

[0005] CN106916989A discloses a method for preparing an alloy material with activated carbon-loaded silicon nanowires. The activated carbon is loaded with silicon nanowires to increase its antistatic ability, the alloy is processed into a foamed aluminum-magnesium alloy preform, and the antistatic filler is vacuum-infiltrated into the alloy, and the finished product is obtained after secondary sintering, which improves the agglomeration phenomenon of the antistatic filler in the alloy material, but the agglomeration problem of silicon nanowires in other materials has not been solved.

[0006] Generally speaking, the agglomeration of SiNWs is mainly caused by the following aspects: First, the high specific surface area, surface energy and van der Waals force brought by the SiNWs nanostructure. In order to greatly reduce the Gibbs free energy of the material, the system attracts each other under the action of the entropy effect, resulting in the agglomeration of particles. Second, static electricity is easily generated between nanomaterial particles, and agglomeration is caused by electrostatic attraction or repulsion. Third, the surface of SiNWs is easily oxidized, and agglomeration occurs under the action of hydrogen bonds and hydration. Fourth, the physical characteristics of the SiNWs linear structure, the long lines are prone to interweaving and entanglement, thus causing agglomeration.

[0007] Therefore, how to promote the dispersion and structure construction of silicon nanowires and realize the large-scale production of silicon nanowires is an important research direction in this field. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a three-dimensional network structure silicon nanowire and its preparation method and application. The preparation method of the three-dimensional network structure silicon nanowire provided by the present invention obtains a uniformly dispersed and structurally stable silicon nanowire electrode material by controlling the wire length of the silicon nanowire, reducing the surface activity, preventing further oxidation and structural reconstruction, while improving the electron and ion transmission performance of the silicon nanowire, reducing the volume expansion rate of the silicon nanowire, and providing a basis for subsequent processing and application in lithium batteries.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] One of the purposes of the present invention is to provide a method for preparing three-dimensional network structured silicon nanowires, the preparation method comprising the following steps:

[0011] (1) after a dispersant and a solvent are first mixed, silicon nanowires are added and secondly mixed to obtain a mixed solution;

[0012] (2) dispersing and separating the mixed solution of step (1) to obtain an intermediate product;

[0013] (3) mixing the intermediate product of step (2) with a building agent, subjecting the mixture to a hydrothermal reaction and then grinding and crushing the mixture to obtain the three-dimensional network structured silicon nanowires.

[0014] The present invention adopts the method of adding a dispersant to a silicon nanowire and a solvent system to obtain a mixed solution, controlling the length of the silicon nanowire after dispersion in step (2), and finally adding a structuring agent in step (3) to realize evaporation self-assembly of the silicon nanowire, thereby preparing a uniformly dispersed three-dimensional network structure of silicon nanowires. In step (3), the structuring agent is added to the intermediate product to prepare the silicon nanowire by hydrothermal reaction, which not only realizes the construction of a three-dimensional conductive network of the silicon nanowire, but also provides a buffer space for the volume change of the silicon nanowire during the process of lithium insertion and extraction, preventing the active material from falling off the current collector, and improving the conductivity and cycle performance of the silicon nanowire.

[0015] In the process of preparing the three-dimensional network structure silicon nanowires, no toxic substances are introduced, the preparation process is simple to operate, and is suitable for large-scale production.

[0016] As a preferred technical solution of the present invention, the dispersant in step (1) includes perfluoropolyether.

[0017] The present invention uses perfluoropolyether as a dispersant for the silicon nanowire system because the F element in the perfluoropolyether has a very strong electronegativity, which can achieve a good dispersing effect. The perfluoropolyether has a low surface tension, good physical and chemical stability, strong hydrophobicity, and can adhere to the surface of the silicon nanowire to form a protective layer. While dispersing the silicon nanowire, it can isolate oxygen and water, thereby preventing the silicon nanowire from being oxidized during subsequent processing, thereby improving the stability of the material. In addition, the F element in the perfluoropolyether can combine with lithium ions to form stable LiF, which improves the stability and cycle performance of the SEI film.

[0018] Preferably, the solvent in step (1) comprises tetrahydrofuran and / or acetone.

[0019] In the present invention, since silicon nanowires are highly active and easily oxidized in water and air, tetrahydrofuran and / or acetone are used as solvents to avoid direct contact between silicon nanowires and oxygen and water. After the silicon nanowires are dispersed, a protective film is formed on the surface thereof, which can effectively prevent the silicon nanowires from being oxidized by the heat generated during ball milling and ultrasound, facilitate subsequent processing, and reduce irreversible phases such as Li2SiO4 and L2O generated by surface oxidation of the silicon nanowires, thereby improving the first coulombic efficiency of the material.

[0020] Preferably, the silicon nanowires in step (1) are prepared by a gas-liquid-solid method.

[0021] Preferably, the diameter of the silicon nanowires in step (1) is 50 to 200 nm, wherein the diameter may be 50 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm or 200 nm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the length of the silicon nanowire in step (1) is 500 to 4000 nm, wherein the length may be 500 nm, 1000 nm, 1500 nm, 2000 nm, 2500 nm, 3000 nm, 3500 nm or 4000 nm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the mass ratio of the dispersant and the silicon nanowires in step (1) is (0.05-5):(95-99.95), wherein the mass ratio can be 0.05:99.95, 0.1:99.9, 0.5:99.5, 1:99, 1.5:98.5, 2:98, 2.5:97.5, 3:97, 3.5:96.5, 4:96, 4.5:95.5 or 5:95, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the mass ratio of the dispersant to the solvent in step (1) is (0.1-0.5):(99.5-99.9), wherein the mass ratio can be 0.5:99.5, 0.4:99.6, 0.3:99.7, 0.2:99.8 or 0.1:99.9, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] As a preferred technical solution of the present invention, the speed of the first mixing in step (1) is 800-1400 r / min, wherein the speed can be 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min or 1400 r / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the time for the first mixing in step (1) is 30 to 60 min, wherein the time can be 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, 42 min, 44 min, 46 min, 48 min, 50 min, 52 min, 54 min, 56 min, 58 min or 60 min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] As a preferred technical solution of the present invention, the speed of the second mixing in step (1) is 800-1500 r / min, wherein the speed can be 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min, 1400 r / min or 1500 r / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] Preferably, the second mixing time in step (1) is 60 to 120 min, wherein the time can be 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] Preferably, the solid content of the mixed liquid in step (1) is 1 to 8%, wherein the solid content can be 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] As a preferred technical solution of the present invention, the dispersion in step (2) includes ball milling and / or ultrasonic treatment.

[0031] In the present invention, after the silicon nanowires are dispersed with a dispersant, they are further dispersed by ball milling and / or ultrasonic treatment to control the length of the silicon nanowires. The process is simple, the requirements for equipment are very low, and there is no need to provide an additional vacuum environment or protective atmosphere. After the silicon nanowires are ball milled and / or ultrasonically treated, the length of the silicon nanowires can be controlled to be less than 20 μm by controlling the treatment time and power. No other substances are introduced and the silicon nanowires themselves will not be affected.

[0032] Preferably, the ball-to-material ratio of the ball mill is (1.5-3.0):1, wherein the ball-to-material ratio can be 1.5:1, 1.8:1, 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1 or 3.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the grinding balls of the ball mill are made of zirconium balls.

[0034] Preferably, the ball milling speed is 300-800 r / min, wherein the speed may be 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min or 800 r / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] Preferably, the ball milling time is 10 to 60 min, wherein the time can be 10 min, 20 min, 30 min, 40 min, 50 min or 60 min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the frequency of the ultrasonic treatment is 20 to 40 kHz, wherein the frequency can be 20 kHz, 22 kHz, 24 kHz, 26 kHz, 28 kHz, 30 kHz, 32 kHz, 34 kHz, 36 kHz, 38 kHz or 40 kHz, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the ultrasonic treatment time is 5 to 30 min, wherein the time can be 5 min, 10 min, 15 min, 20 min, 25 min or 30 min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the intermittent frequency of the ultrasonic treatment is 3 to 7 seconds / time, wherein the intermittent frequency can be 3 seconds / time, 4 seconds / time, 5 seconds / time, 6 seconds / time or 7 seconds / time, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] As a preferred technical solution of the present invention, the separation in step (2) includes screening and / or centrifugation.

[0040] Preferably, the mesh number of the sieving is 70-90 mesh, wherein the mesh number can be 70 mesh, 72 mesh, 74 mesh, 76 mesh, 78 mesh, 80 mesh, 82 mesh, 84 mesh, 86 mesh, 88 mesh or 90 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] As a preferred technical solution of the present invention, the builder in step (3) includes a polyether solution.

[0042] The present invention adopts a polyether solution as a construction agent for the silicon nanowire structure. The polyether solution can form micelles at a certain concentration. The three-dimensional structure of the silicon nanowire can be constructed only through simple hydrothermal reaction evaporation self-assembly, thereby improving the conductivity and structural stability of the silicon nanowire. At the same time, the polyether solution also has excellent dispersibility, which can avoid secondary agglomeration of the silicon nanowire during the structural reconstruction process.

[0043] Preferably, the method for preparing the polyether solution comprises: dissolving polyether in water to obtain the polyether solution.

[0044] Preferably, the molar concentration of the polyether solution is 0.05 to 0.1 mol / L, wherein the molar concentration may be 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L or 0.1 mol / L, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, the solid content of the intermediate product in step (3) in the structuring agent is 1-5%, wherein the solid content can be 1%, 2%, 3%, 4% or 5%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0046] Preferably, the temperature of the hydrothermal reaction in step (3) is 60-80°C, wherein the temperature can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Preferably, the time of the hydrothermal reaction in step (3) is 5 to 10 hours, wherein the time can be 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the intermediate product is stirred during the hydrothermal reaction in step (3).

[0049] Preferably, the stirring speed is 800-1400 r / min, wherein the speed may be 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min or 1400 r / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the particle size of the three-dimensional network structure silicon nanowires in step (3) is ≤25 μm, wherein the particle size can be 5 μm, 10 μm, 15 μm, 20 μm or 25 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] Preferably, in step (3), D of the three-dimensional network structured silicon nanowires 50 The particle size is 5 to 10 μm, wherein the particle size can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] As a preferred technical solution of the present invention, the preparation method comprises:

[0053] (1) After a first mixing of perfluoropolyether and a solvent, wherein the first mixing rate is 800 to 1400 r / min and the time is 30 to 60 min, silicon nanowires are added for a second mixing to obtain a mixed solution with a solid content of 1 to 8%, wherein the second mixing rate is 800 to 1500 r / min and the time is 60 to 120 min;

[0054] (2) dispersing and separating the mixed solution of step (1) to obtain an intermediate product;

[0055] (3) adding the intermediate product of step (2) to a polyether solution with a molar concentration of 0.05 to 0.1 mol / L, performing a hydrothermal reaction, and then grinding and crushing the intermediate product to obtain the three-dimensional network structure silicon nanowire with a particle size of ≤25 μm, stirring the intermediate product during the hydrothermal reaction at a speed of 800 to 1400 r / min, and performing the hydrothermal reaction at a temperature of 60 to 80° C. for 5 to 10 h.

[0056] The second object of the present invention is to provide a three-dimensional network structure silicon nanowire, and the three-dimensional network structure silicon nanowire is prepared by the preparation method as described in the first object.

[0057] The particle size of the three-dimensional network structure silicon nanowires is ≤25 μm, wherein the particle size can be 5 μm, 10 μm, 15 μm, 20 μm or 25 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] Preferably, in step (3), D of the three-dimensional network structured silicon nanowires 50 The particle size is 5 to 10 μm, wherein the particle size can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] The third object of the present invention is to provide a lithium-ion battery comprising the three-dimensional network structured silicon nanowires as described in the second object.

[0060] Compared with the prior art, the present invention has the following beneficial effects:

[0061] (1) A dispersant is added to a silicon nanowire and a solvent system to obtain a mixed solution, and the length of the silicon nanowire is controlled, the surface activity is reduced, and further oxidation and structural reconstruction are prevented to obtain a uniformly dispersed and structurally stable silicon nanowire electrode material. A structuring agent is added during the preparation process to realize the evaporation self-assembly of the silicon nanowire, thereby preparing a uniformly dispersed three-dimensional network structure of silicon nanowires. The structuring agent is added to the intermediate product and the silicon nanowire is prepared by hydrothermal reaction, which not only realizes the construction of a three-dimensional conductive network of the silicon nanowire, but also provides a buffer space for the volume change of the silicon nanowire during the process of lithium insertion and extraction, prevents the active material from falling off the current collector, and improves the conductivity and cycle performance of the silicon nanowire.

[0062] (2) In the process of preparing the three-dimensional network structure silicon nanowires, no toxic substances are introduced, the preparation process is simple to operate, and is suitable for large-scale production. DETAILED DESCRIPTION

[0063] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0064] Example 1

[0065] This embodiment provides a method for preparing three-dimensional network structured silicon nanowires, the preparation method comprising:

[0066] 1. Ingredients: Calculate and weigh the amount of PFPE and SiNWs according to the mass ratio of PFPE (perfluoropolyether): SiNWs (obtained by VLS method) of 2.5:97.5.

[0067] 2. Mixing: PFPE and tetrahydrofuran were first mixed and stirred evenly, wherein the speed of the first mixing was 1100 r / min and the stirring time of the first mixing was 45 min. After the first mixing was completed, SiNWs were added for a second mixing to obtain a mixed solution with a solid content of 4.5%, wherein the speed of the second mixing was 1250 r / min and the time was 90 min.

[0068] 3. Dispersion and separation: transfer the above mixed liquid and grinding balls into a ball mill for dispersion, weigh the grinding balls according to the ratio of ball to material of 2.2:1 (the mass of the material is calculated according to the mass of the slurry after stirring). The grinding balls are made of zirconium balls, and the mass ratio of grinding balls of different diameters is Φ1:Φ3:Φ5:Φ8:Φ10=25:25:25:15:10. The ball milling conditions are: speed 550r / min, time 35min.

[0069] The dispersed slurry was sieved through an 80-mesh screen to separate the pellets and obtain an intermediate product.

[0070] 4. Reconstruction of three-dimensional network structure: Take a certain amount of F-127 (polyether) and dissolve it in deionized water with a molar concentration of 0.08 mol / L. Add the intermediate product separated above for hydrothermal reaction (wherein the solid content of the intermediate product in the polyether solution is 2.5%), rotate at 1100 r / min, and the temperature of the hydrothermal reaction is 70°C for 8 hours. Evaporate the water to realize the self-assembly of SiNWs structure. After grinding and crushing, a powder with a particle size of ≤25 μm is obtained. Powder D 50 =7.5μm.

[0071] Example 2

[0072] This embodiment provides a method for preparing three-dimensional network structured silicon nanowires, the preparation method comprising:

[0073] 1. Ingredients: Calculate and weigh the amount of PFPE and SiNWs according to the mass ratio of PFPE (perfluoropolyether): SiNWs (obtained by VLS method) of 0.05:99.95.

[0074] 2. Mixing: PFPE and acetone were mixed and stirred evenly for the first time, wherein the speed of the first mixing was 800 r / min and the stirring time of the first mixing was 60 min. After the first mixing was completed, SiNWs were added for the second mixing to obtain a mixed solution with a solid content of 1%, wherein the speed of the second mixing was 800 r / min and the stirring time was 120 min.

[0075] 3. Dispersion and separation: transfer the above mixed liquid and grinding balls into a ball mill for dispersion, and weigh the grinding balls at a ratio of 1.5:1 (the mass of the material is calculated based on the mass of the slurry after stirring). The grinding balls are made of zirconium balls, and the mass ratio of grinding balls of different diameters is Φ1:Φ3:Φ5:Φ8:Φ10=5:40:30:15:10. The ball milling conditions are: speed 300r / min, time 60min.

[0076] The dispersed slurry was sieved through an 80-mesh screen to separate the pellets and obtain an intermediate product.

[0077] 4. Reconstruction of three-dimensional network structure: Take a certain amount of F-127 (polyether) and dissolve it in deionized water with a molar concentration of 0.05 mol / L. Add the intermediate product separated above for hydrothermal reaction (wherein the solid content of the intermediate product in the polyether solution is 1%), rotate at 800 r / min, and the temperature of the hydrothermal reaction is 60°C for 10 h. Evaporate the water to realize the self-assembly of SiNWs structure. After grinding and crushing, a powder with a particle size of ≤25 μm is obtained. Powder D 50 =5μm.

[0078] Example 3

[0079] This embodiment provides a method for preparing three-dimensional network structured silicon nanowires, the preparation method comprising:

[0080] 1. Ingredients: Calculate and weigh the amount of PFPE and SiNWs according to the mass ratio of PFPE (perfluoropolyether): SiNWs (obtained by VLS method) of 5:95.

[0081] 2. Mixing: PFPE and tetrahydrofuran were first mixed and stirred evenly, wherein the speed of the first mixing was 1400 r / min and the stirring time of the first mixing was 30 min. After the first mixing was completed, SiNWs were added for a second mixing to obtain a mixed solution with a solid content of 8%, wherein the speed of the second mixing was 1500 r / min and the stirring time was 60 min.

[0082] 3. Dispersion and separation: The above mixed solution is transferred into an ultrasonic machine for dispersion. The ultrasonic conditions are: frequency of 30kHz, time of 18min, and intermittent frequency of 5 seconds / time.

[0083] The ultrasonic-treated mixture is centrifuged and the organic solvent is recovered to obtain an intermediate product.

[0084] 4. Reconstruction of three-dimensional network structure: Take a certain amount of F-127 (polyether) and dissolve it in deionized water with a molar concentration of 0.1 mol / L. Add the intermediate product separated above for hydrothermal reaction (wherein the solid content of the intermediate product in the polyether solution is 5%), rotate at 1400 r / min, and the temperature of the hydrothermal reaction is 80°C for 5 h. Evaporate the water to realize the self-assembly of SiNWs structure. After grinding and crushing, a powder with a particle size of ≤25 μm is obtained. Powder D 50 =10μm.

[0085] Example 4

[0086] In this example, except that the perfluoropolyether in the batching and mixing steps is replaced by perfluorooctanoic acid, other conditions are the same as those in Example 1.

[0087] Example 5

[0088] In this embodiment, except that tetrahydrofuran in the mixing step is replaced by acetone, other conditions are the same as those in embodiment 1.

[0089] Example 6

[0090] In this example, except that the polyether in the three-dimensional network structure reconstruction step is replaced by sodium carboxymethyl cellulose, other conditions are the same as those in Example 1.

[0091] Comparative Example 1

[0092] In this comparative example, except that the steps of mixing, dispersing and separating are not performed, and the perfluoropolyether and silicon nanowires are directly ground and then used as intermediate products to undergo hydrothermal reaction with the building agent, other conditions are the same as those in Example 1.

[0093] Comparative Example 2

[0094] This comparative example directly uses raw silicon nanowires as electrode materials.

[0095] The silicon nanowires prepared in Examples 1-6 and Comparative Example 1 and the silicon nanowires in Comparative Example 2 were used as electrodes to assemble lithium ion half-cells for impedance (R ct ) and cycle performance tests. Among them, the metal lithium sheet is the counter electrode, celgard-2400 is the diaphragm, the electrolyte is 1mol / L LiPF6 dissolved in EC:DEC:EMC (volume ratio of 1:1:1), assembled into a CR2032 button cell to test the impedance and cycle performance of the lithium-ion battery, wherein the impedance test conditions are 0.01-100000Hz, and the amplitude is 0.01V. The test conditions for cycle performance are voltage range 0.01-0.8V, current density 0.2C, and 100 cycles. The test results are shown in Table 1.

[0096] Table 1

[0097]

[0098] From the above table, it can be seen that the use of perfluoropolyether and F127 to disperse silicon nanowires and construct three-dimensional structures can effectively improve the cycle performance of silicon nanowires and reduce their impedance. The concentration of perfluoropolyether has a great influence on the electrochemical properties of the final product. The appropriate concentration of perfluoropolyether can effectively improve the dispersion of SiNWs, reduce their agglomeration and thus improve the cycle performance.

[0099] By comparing Example 1 and Example 4, it can be seen that the dispersion performance of perfluoropolyether on SiNWs is better than that of perfluorooctanoic acid.

[0100] By comparing Example 1 with Example 5, it can be seen that both tetrahydrofuran and acetone can play a good solvent role, but the effect of tetrahydrofuran is more excellent.

[0101] By comparing Example 1 and Example 6, it can be seen that polyether is more beneficial to the electrochemical performance of the material than sodium carboxymethyl cellulose.

[0102] By comparing Example 1 with Comparative Example 1, it can be seen that if the steps of mixing, dispersing and separating are not performed, the electrochemical performance of the prepared silicon nanowires will decrease.

[0103] By comparing Example 1 with Comparative Example 2, it can be seen that the method for preparing silicon nanowires of the present invention has greatly improved performance compared with traditional silicon nanowires on the market.

[0104] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing three-dimensional network structured silicon nanowires, characterized in that: The preparation method comprises the following steps: (1) after a dispersant and a solvent are first mixed, silicon nanowires are added and secondly mixed to obtain a mixed solution; (2) dispersing and separating the mixed solution of step (1) to obtain an intermediate product; (3) mixing the intermediate product of step (2) with a building agent, subjecting the mixture to a hydrothermal reaction and then grinding and crushing the mixture to obtain the three-dimensional network structured silicon nanowires.

2. The preparation method according to claim 1, characterized in that: The dispersant in step (1) comprises perfluoropolyether; Preferably, the solvent in step (1) comprises tetrahydrofuran and / or acetone; Preferably, the silicon nanowires in step (1) are prepared by a gas-liquid-solid method; Preferably, the diameter of the silicon nanowires in step (1) is 50 to 200 nm; Preferably, the length of the silicon nanowire in step (1) is 500 to 4000 nm; Preferably, the mass ratio of the dispersant to the silicon nanowires in step (1) is (0.05-5):(95-99.95); Preferably, the mass ratio of the dispersant to the solvent in step (1) is (0.1-0.5):(99.5-99.9).

3. The preparation method according to claim 1 or 2, characterized in that: Step (1) The first mixing speed is 800-1400 r / min; Preferably, the first mixing time in step (1) is 30 to 60 minutes.

4. The preparation method according to any one of claims 1 to 3, characterized in that Step (1) the second mixing speed is 800-1500 r / min; Preferably, the second mixing time in step (1) is 60 to 120 minutes; Preferably, the solid content of the mixed solution in step (1) is 1 to 8%.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The dispersion in step (2) comprises ball milling and / or ultrasonic treatment; Preferably, the ball-to-material ratio of the ball mill is (1.5-3.0):1; Preferably, the grinding balls of the ball mill are made of zirconium balls; Preferably, the ball milling speed is 300-800 r / min; Preferably, the ball milling time is 10 to 60 minutes; Preferably, the frequency of the ultrasonic treatment is 20 to 40 kHz; Preferably, the ultrasonic treatment time is 5 to 30 minutes; Preferably, the intermittent frequency of the ultrasonic treatment is 3 to 7 seconds per time.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The separation in step (2) comprises screening and / or centrifugation; Preferably, the mesh size of the sieving is 70 to 90 meshes.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The builder in step (3) comprises a polyether solution; Preferably, the method for preparing the polyether solution comprises: dissolving the polyether in water to obtain the polyether solution; Preferably, the molar concentration of the polyether solution is 0.05 to 0.1 mol / L; Preferably, the solid content of the intermediate product in the structuring agent in step (3) is 1 to 5%; Preferably, the temperature of the hydrothermal reaction in step (3) is 60-80°C; Preferably, the hydrothermal reaction time in step (3) is 5 to 10 hours; Preferably, the intermediate product is stirred during the hydrothermal reaction in step (3); Preferably, the stirring speed is 800-1400 r / min; Preferably, the particle size of the three-dimensional network structure silicon nanowires in step (3) is ≤25 μm; Preferably, in step (3), D of the three-dimensional network structured silicon nanowires 50 The particle size is 5 to 10 μm.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises: (1) After a first mixing of perfluoropolyether and a solvent, wherein the first mixing rate is 800 to 1400 r / min and the time is 30 to 60 min, silicon nanowires are added for a second mixing to obtain a mixed solution with a solid content of 1 to 8%, wherein the second mixing rate is 800 to 1500 r / min and the time is 60 to 120 min; (2) dispersing and separating the mixed solution of step (1) to obtain an intermediate product; (3) adding the intermediate product of step (2) to a polyether solution with a molar concentration of 0.05 to 0.1 mol / L, performing a hydrothermal reaction, and then grinding and crushing the intermediate product to obtain the three-dimensional network structure silicon nanowire with a particle size of ≤25 μm, stirring the intermediate product during the hydrothermal reaction at a speed of 800 to 1400 r / min, and performing the hydrothermal reaction at a temperature of 60 to 80° C. for 5 to 10 h.

9. A three-dimensional network structured silicon nanowire, characterized in that: The three-dimensional network structured silicon nanowires are prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery contains the three-dimensional network structure silicon nanowire as claimed in claim 9.

Citation Information

Patent Citations

  • Self-dispersing silicon nano-wire powder prepared by mechanical alloying aided solid-liquid-solid method

    CN104003393A

  • Preparation method for alloy material with activated carbon loaded silicon nanowires

    CN106916989A